Nexus between energy usability, economic indicators and environmental sustainability in four asean countries: A non-linear autoregressive exogenous neural network modelling approach - Mustapa S.I.; Ayodele F.O.; Ayodele B.V.; Mohammad N. (MDPI AG, 2023)
This study investigates the use of a non-linear autoregressive exogenous neural network (NARX) model to investigate the nexus between energy usability, economic indicators, and carbon dioxide (CO2) emissions in four Association of South East Asian Nations (ASEAN), namely Malaysia, Thailand, Indonesia, and the Philippines. Optimized NARX model architectures of 5-29-1, 5-19-1, 5-17-1, 5-13-1 representing the input nodes, hidden neurons and the output units were obtained from the series of models configured. Based on the relationship between the input variables, CO2 emissions were predicted with a high correlation coefficient (R) > 0.9. and low mean square errors (MSE) of 3.92 10?21, 4.15 10?23, 2.02 10?19, 1.32 10?20 for Malaysia, Thailand, Indonesia, and the Philippines, respectively. Coal consumption has the highest level of influence on CO2 emissions in the four ASEAN countries based on the sensitivity analysis. These findings suggest that government policies in the four ASEAN countries should be more intensified on strategies to reduce CO2 emissions in relationship with the energy and economic indicators. 2020 by the authors. Licensee MDPI, Basel, Switzerland.